Landscapes of activism : civil society and HIV and AIDS care in northern Mozambique - Reed, Joel Christian (Medical anthropology (New Brunswick, N.J.), 2018)
AIDS activists are often romanticized as extremely noble and selfless. However, the relationships among HIV support group members highlighted in Landscapes of Activism are hardly utopian or ideal. Reed shows that in Africa, superimposing a Western idea of what activism should look like actually hampers the success of these groups.